Fundraising and online marketing: how social media have an impact on the growth of a charity organization - Tonetti, Andrea (2019)
The main aim of this dissertation is to study how digital marketing techniques can be implemented in the fundraising strategy of non-profit organizations, and how to face the transition from an old school fundraising approach to a digital one. During the past decade, the internet and social media deeply changed the way non-profit organizations approach fundraising. Digital communication became quick, multilateral and dynamic, thus making the mass communication techniques adopted until that period obsolete. In this context, organizations must adapt to be able to implement successful marketing strategies and collect the funds necessary for their own development. The biggest challenges are the lack of specialized professional figures in digital fundraising and the difficulty in keeping up with the rapid digital developments in the communication and marketing field. This dissertation is divided into 6 main parts: The introduction, where the topic and the aim of the work are presented. Chapter 1, addressing academic background for fundraising and the challenges that currently exist in the digital world. Chapter 2, giving an overview of the current situation of digital adoption across non-profits all over the world. Chapter 3, where the differences between the main social media platforms are presented, as well as the guidelines to use them in order to produce an effective content strategy. Chapter 4, where strategies and best practices of non-profit digital fundraising are analyzed in details and compared with the classical methods. The conclusion, where recommendations for regulators and practitioners are presented.